A cross sectional study of maternal near miss and mortality at a rural tertiary centre in southern nigeria - Ikechukwu Innocent Mbachu; Chukwuemeka Ezeama; Kelechi Osuagwu; Osita Samuel Umeononihu; Chibuzor Obiannika; Nkeiru Ezeama (BMC, 2017)
Abstract Background The study evaluated the pattern of severe maternal outcome, near miss indicators and associated patient and healthcare factors at a private referral hospital in rural Nigeria. Methods This was a cross sectional study conducted from September 2014 to August 2015 in Madonna University Teaching Hospital Elele, Rivers State, Nigeria. Pregnant and postpartum women were recruited for the study using Nigeria near miss network proforma which was adopted from the WHO near miss proforma. We explored administrative, patient related and medical delays. Statistical analysis was done using SPSS version 20. Results Of the 262 deliveries, 5 women died and 52 women had a near miss event. The maternal mortality rate was 1908/100,000. The maternal near miss mortality ratio was 11.4: 1 while the mortality index was 8.8%. Three out of the five deaths that occurred were in the age category of 20-24 years. Abortive outcome was the leading cause of maternal mortality contributing 2 of the 5 maternal mortality. The severe maternal outcome ratio was 218/1000 and maternal near miss incidence ratio was 198/1000. Hypertensive disorders of pregnancy contributed 16(28.1%) of the 57 cases with severe maternal outcome while Obstetrics hemorrhage and abortive outcome each contributed 14(24.6%). 6(10.5%) received treatment within 30 min of diagnosis while 19(33.3%) waited for greater than 240 min before they received intervention. There was a statistically significant association between time of intervention and final maternal outcome (p-value = 0.003). Administrative delay was noted in 20 cases, while patient related delay was noted in 44 cases. Conclusion There is a high burden of near miss and unmet need for reproductive health services in rural areas of Nigeria. Different levels of delays abound and contribute to the disease burden. Periodic reviews will aid in elimination of the delays. There should be better communication between different levels of care and emphasis should be on early identification and referral of women for prompt management.